"I Want My Mum to Know That I Am a Good Guy …": A Thematic Analysis of the Accounts of Adolescents Who Exhibit Child-to-Parent Violence in the United Kingdom - Papamichail, Alexandra (Journal of interpersonal violence, 2022)
This qualitative study explores child-to-parent violence (CPV) in the United Kingdom based on the accounts of adolescents who exhibit this type of family violence. The key areas of interest concern the familial relationships and contexts within which adolescents are embedded, and their perceptions about their emotional states and how these interplay with CPV. Eight participants were recruited in total from a community sample from two different intervention programs aiming to tackle CPV in England. Methods included participant-observation, face-to-face interviews, and handwritten interviews; all data were analyzed thematically. Results suggest that CPV is linked with adverse childhood experiences (ACEs), unsatisfactory relationships with parents, perceived emotional rejection from parents, and emotional dysregulation in young people. In this study, violent behavior was directed not only against mothers but in all cases against siblings and stepfathers. The findings address the complexity of the subject and the need for tailored, evidence-based interventions in the field of CPV.